Incineration or pulverization? Evolutionary game model of management of nematode-infected pine wood in China in the carbon neutrality context - Wen, Xuanye; Gu, Tianlu; Qi, Huan; Zhang, Feiping (Frontiers in Environmental Science, 2022)
The rapid spread of pine wilt disease has become a major crisis with regard to forest ecological security. Against the background of China’s concerted effort to achieve carbon neutrality by 2060, balancing economic and environmental costs during the environmentally sound treatment of nematode-infected pine wood is an issue worthy of attention. In this study, we constructed an evolutionary game model of the central government, local governments, and infected wood management-related enterprises and analyzed the evolutionary process of the three parties with stable strategies based on a full consideration of actual circumstances. To verify the theoretical results, we conducted numerical simulations using MATLAB. The results of the study are as follows. (1) The central government plays a decisive role in how infected wood is handled. The greater the degree of regulation is, the greater the local government favors low carbon emissions and the more companies will choose the pulverization method. (2) Local governments bear the main responsibility in the processing of infected wood, and only when local governments are sufficiently penalized will enterprises choose to pulverize the wood and dispose of it. (3) Policy subsidies are an effective measure that will help the three parties in the model reach a balance more quickly. Overall, this study clarified the realization path of low-carbon treatment of nematode-infected pine wood from a policy perspective. The study results should help promote the low-carbon treatment of nematode-infected pine wood and provide a basis for the formulation of relevant forestry policies in the context of carbon neutrality.